Rapamycin Modulates the Proinflammatory Memory-Like Response of Microglia Induced by BAFF - Wang, Jianing; Yang, Chunshu; Hou, Xiaoyu; Xu, Jingyi; Yun, Yang; Qin, Ling; Yang, Pingting (Frontiers in Immunology, 2021)
Background: Recently trained immunity of microglia provided an opportunity to study the chronic effect of microglial activation and its metabolic rewiring in neuroimmunological diseases. Since elevated levels of B cell-activating factor (BAFF) have been proved to be associated with some chronic neuroimmunological disorders. Here, we used the trained innate immunity model to analyze the effect of BAFF, a vital regulator of the adaptive immune system, on long-term microglial activation and metabolic reprogramming in vitro and in vivo. Methods and results: In Vitro, BV2 cells and mouse primary microglial cells were incubated with BAFF for 24 h(BAFF priming). After 5 days of resting, microglia were restimulated with LPS(LPS restimulation) or BAFF(BAFF restimulation). BAFF priming induced a pro-inflammatory trained immunity-phenotype of both BV2 cells and primary microglial cells, which was indicated by morphological change, secretion of pro-inflammatory cytokine and chemokine upon LPS restimulation or BAFF restimulation. The production of lactate and NAD+/NADH ratio were elevated 5 days after BAFF priming. The activation of the Akt/mTOR/HIF-1α pathway was induced by BAFF priming and lasted for 5 days. Pretreating the BV2 cells or mouse primary microglial cells with rapamycin blocked mTOR/HIF-1α activation and cellular metabolic reprogramming induced by BAFF training. Consistently, rapamycin efficiently suppressed the trained immunity-like responses of microglia triggered by BAFF. In vivo, adult male mice were treated withBAFF by intracerebroventricular injection for priming and 7 days later with BAFF for restimulation. BAFF training activated microglia in the cortex and hippocampus. The production of proinflammatory cytokines and chemokines was elevated after BAFF training. Conclusion: Our current data, for the first time, demonstrate that BAFF priming induces a proinflammatory memory-like response of microglia not only to LPS but also to BAFF itself. Rapamycin inhibits microglial priming triggered by BAFF through targeting the mTOR/HIF-1α signaling pathway. Our data reveal a novel role of BAFF in trained immunity and that rapamycin may be a potential therapeutic target of neuroimmunological diseases.